Coping Strategies and the Burden of Caring for Family Members on the Quality of Life of Families of Leukemia Patients - Khaira, Niswatul; Ichwansyah, Fahmi; Zulfan, Zulfan (Indonesian Journal of Global Health Research, 2025)
The life of families caring for members with leukemia can be disrupted due to the high burden of care, thus risking a decrease in quality of life. This study aims to analyze the relationship between coping strategies and burden of care with the quality of life of families with leukemia at the Banda Aceh City Shelter. The study used a cross-sectional design with a total of 55 respondents taken through a total sampling technique from five shelters. Data collection was carried out through interviews using questionnaires from August 10 to September 10, 2023. Data analysis was carried out bivariately and multivariately using ordinal logistic regression. The results showed that 56.36% of respondents had a poor quality of life. Coping strategies, burden of care, social support, self-efficacy, education, employment, income, gender, and age were related to quality of life, while marital status was not. Respondents with low quality of life used more emotional focused coping strategies (65.85%) than problem focused coping (28.57%) (OR=4.82; p=0.020). In addition, heavy caregiving burden increases the risk of poor quality of life up to 11 times (OR=11; p=0.007). Multivariate analysis showed that the most dominant factor was family income. Therefore, the use of halfway houses is highly recommended to reduce the economic burden of cancer patients' families.